PENGARUH BUDAYA KERJA, KUALITAS PELAYANAN, SARANA DAN PRASARANA TERHADAP KEPUASAN MASYARAKAT - Fahmy Idris; Salju Salju (Kelola: Journal of Islamic Education Management, 2023)
The satisfaction of the community is a very important factor and determines the success of a business entity because the public are consumers of the products or services it generates. Problems found in the study are the complaints about the lack of visitors going to the Ministry as well as the facilities and infrastructure that are going on in Immigration Office Class III Non TPI Of Palopo, so the impact on the number of visitors Immigration Office Class III Non TPI Of Palopo. This study aims to analyze the quality of service provided to the public health center or community Immigration Office Class III Non TPI Of Palopo and to determine the level of conformity between the performance of the Ministry of public health with the hope of Community importance or use of the service. Analysis tools are used is to use the community's Satisfaction Index (IKM). Community satisfaction (IKM) is calculated using the weighted average value of each item of service in accordance with the decision of the Minister for Administrative Reform No. 25 of 2004. The methods used to determine the level of conformity is a method of Importance Performance Analysis (IPA). The Research Community Satisfaction Index measurement (IKM) indicates the quality of the given services Immigration Office Class III Non TPI Of Palopo still less well, based on the average value of the elements of each service unit at the clinic. Form comparisons between expectations and performance service levels, there are some elements that should be prioritized as elements of service, speed and commitmen because in fact the community still feel lack of commitmen employees of Immigration Office Class III Non TPI Of Palopo in serving the community.